An ex vivo test to investigate genetic factors conferring susceptibility to atypical haemolytic uremic syndrome - Gastoldi, Sara; Aiello, Sistiana; Galbusera, Miriam; Breno, Matteo; Alberti, Marta; Bresin, Elena; Mele, Caterina; Piras, Rossella; Liguori, Lucia; Santarsiero, Donata; Benigni, Ariela; Remuzzi, Giuseppe; et al. (Frontiers in Immunology, 2023)
Comprehensive genetic analysis is essential to clinical care of patients with atypical haemolytic uremic syndrome (aHUS) to reinforce diagnosis, and to guide treatment. However, the characterization of complement gene variants remains challenging owing to the complexity of functional studies with mutant proteins. This study was designed: 1)To identify a tool for rapid functional determination of complement gene variants; 2)To uncover inherited complement dysregulation in aHUS patients who do not carry identified gene variants. To address the above goals, we employed an ex-vivo assay of serum-induced C5b-9 formation on ADP-activated endothelial cells in 223 subjects from 60 aHUS pedigrees (66 patients and 157 unaffected relatives). Sera taken from all aHUS patients in remission induced more C5b-9 deposition than control sera, independently from the presence of complement gene abnormalities. To avoid the possible confounding effects of chronic complement dysregulation related to aHUS status, and considering the incomplete penetrance for all aHUS-associated genes, we used serum from unaffected relatives. In control studies, 92.7% of unaffected relatives with known pathogenic variants exhibited positive serum-induced C5b-9 formation test, documenting a high sensitivity of the assay to identify functional variants. The test was also specific, indeed it was negative in all non-carrier relatives and in relatives with variants non-segregating with aHUS. All but one variants in aHUS-associated genes predicted in-silico as likely pathogenic or of uncertain significance (VUS) or likely benign resulted as pathogenic in the C5b-9 assay. At variance, variants in putative candidate genes did not exhibit a functional effect, with the exception of a CFHR5 variant. The C5b-9 assay in relatives was helpful in defining the relative functional effect of rare variants in 6 pedigrees in which the proband carried more than one genetic abnormality. Finally, for 14 patients without identified rare variants, the C5b-9 test in parents unmasked a genetic liability inherited from an unaffected parent. In conclusion, the serum-induced C5b-9 formation test in unaffected relatives of aHUS patients may be a tool for rapid functional evaluation of rare complement gene variants. When combined with exome sequencing the assay might be of help in variant selection, to identify new aHUS-associated genetic factors.